(untitled) (Research, Society and Development, 2023)
Medical Ethics has been increasing its focus on the formal study and analysis of ethical and moral problems encountered in medical practice. The objective of this work was to discuss the importance of ethics in the relationship between physicians and other health professionals. This is a descriptive study, carried out through a narrative review of literature from 2019 to 2023. 14 articles were selected as the corpus of analysis. The ethical principles for resolving conflicts in the hospital work environment involve the development of social skills such as communication, problem solving, cooperation, empathy and assertiveness. The use of the mediation process in the prevention, management and resolution of conflicts in the health area and, in particular, in the areas of competence of clinical, medical and hospital management, brings numerous organizational benefits.